The crystallite-size and distortion сalculation from line integral breadth of powder ... - Bekenova, G. K.; Tursynuly, E.; Slyusarev, A. P.; Eremin, Yu P (Recent Contributions to Physics, 2013)
Crystallite size – blocks of coherent scattering and structural defects of minerals from disseminated ores and products of enrichment at X-ray diffraction study are determined. They are a broadening of the intensity distribution of reflexes, a shift of the diffraction peaks, changes in the integrated intensities in the X-ray diffraction patterns. Integral width of the measured diffraction profile is the sum of the geometric and physical broadening of the lines. Geometric, instrumental broadening (b) due to the divergence of the incident beam, the absorption in the sample, a doublet character Kα radiation, receiving slit size of detector. To find the instrumental broadening is necessary to capture the standard – a standard sample for which the value microstrain ε ≤ 10-4 or dislocation density ρ ≤ 108 cm2 and the block size of the coherent scattering D ≥ 0.2 mm. The value of the physical broadening (β) depends on the microstrain of crystal lattice and dispersion (size) of particles. To determine whether the main cause of the broadening of the diffraction peaks (crystallite size D and microstrain) is necessary to compare the broadening of the two lines that differ only in the order of reflection from one set of planes. The choice of reference materials and methods of primary processing of diffraction spectra allows to determine the instrumental width (b) of the diffraction lines and the experimental data, that are obtained in the measurement of mineral of the dressing products. The techniques of primary processing of diffraction patterns: Fourier smoothing, subtraction Kα2, approximation of the diffraction profile of the reflex by Cauchy, Gauss and Pearson functions for determination of the crystallite size and crystal lattice distortions of minerals from enrichment products of Au-ore Komarovsky deposit are proposed. X-ray diffraction study of samples showed that the suitable method of broadening the following reflections with indexes: 200 – pyrite (2,70 Å); 101 – quartz (3,34 Å); 004 – chlorite (3,51 Å); 104 – dolomite (2,89 Å). As the primary treatment method changes the value of diffraction reflex full width at half maximum, in the calculations from the measured diffractograms of the samples accounted scheme application processing standards. The best convergence of results are observed when using the Gaussian approximation and the calculation program WinFit. The values of the crystallite size and microstrain belong to the area of applicability of the described methods.